2009
DOI: 10.1093/jxb/ern348
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress-induced cell death in the unicellular green alga Micrasterias denticulata

Abstract: Programmed cell death (PCD) is a key element in normal plant growth and development which may also be induced by various abiotic and biotic stress factors including salt stress. In the present study, morphological, biochemical, and physiological responses of the theoretically immortal unicellular freshwater green alga Micrasterias denticulata were examined after salt (200 mM NaCl or 200 mM KCl) and osmotic stress induced by iso-osmotic sorbitol. KCl caused morphological changes such as cytoplasmic vacuolizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 101 publications
12
177
1
1
Order By: Relevance
“…In agreement with this hypothesis, it has been recently shown that autophagosome-like structures are generated as a response to prolonged salt stress in the unicellular green alga Micrasterias denticulata (Affenzeller et al, 2009). However, the molecular features of autophagy have never been characterized in green algae.…”
Section: Discussionmentioning
confidence: 55%
“…In agreement with this hypothesis, it has been recently shown that autophagosome-like structures are generated as a response to prolonged salt stress in the unicellular green alga Micrasterias denticulata (Affenzeller et al, 2009). However, the molecular features of autophagy have never been characterized in green algae.…”
Section: Discussionmentioning
confidence: 55%
“…3). It is well established for microalgae that a slight decrease in F V /F M values during salt and osmotic stress does not bring substantial limitation to photosynthetic processes within the first few hours of salinity stress (Affenzeller et al 2009). Prolonged salt stress, however, may decrease photosynthetic efficiency as shown for salt-stressed green alga Scenedesmus (Demetriou et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, different types of stress such as UV irradiation, osmotic stress, transcriptional inhibition, heat shock and starvation, alter structure of CBs and redistribute coilin and other CB components. 18 It has previously been reported that plant cells exposed to high salt (NaCl), can induce osmotic shock, imbalance in the cellular ion concentration and oxidative stress, 92 which are manifested by increased H 2 O 2 production, accumulation of programmed cell death (PCD) markers, cytosolic cytochrome c leakage and bleaching. 93,94 In order to determine whether coilin and/or CBs can influence such responses to abiotic stress, coilin silenced K D transgenic or non-transgenic tobacco leaf discs were treated with increased concentrations of NaCl.…”
Section: Abiotic Stressmentioning
confidence: 99%